The Impact of Gadget Use on the Social Development of Elementary School Students - Stevanus, Ivan (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to describe the impact of gadget use on the social development of elementary school students. It explores the relationship between gadget usage and the social behaviors of students in grades II and V across four elementary schools in South Jakarta and Central Jakarta. Methods: This study uses a mixed-method approach with a sequential explanatory model. The subjects of the study consisted of 251 elementary school students in grade II and 230 students in grade V. Data were collected through quantitative and qualitative techniques, including questionnaires, interviews, and observations. Quantitative data were analyzed using inferential statistics and presented in the form of tables and charts, while qualitative data were analyzed descriptively. Results: The findings show a significant impact of gadget use on the social development of elementary school students. Regression analysis yielded a significant result (p = 0.000), indicating that gadget use at home and school influences students' social development. Despite the use of gadgets, students remain capable of socializing with their peers, understanding their friends' emotional states, maintaining friendships, recognizing friends' thoughts, attitudes, and feelings, and improving their friends' well-being. Novelty: This study contributes to understanding how the use of gadgets influences the social development of elementary school students, especially in the context of South and Central Jakarta. It is one of the few studies that explore this relationship in a detailed, mixed-method framework and across different school types (public and private), providing valuable insights into developmental changes in social behavior related to gadget usage.